‘absent mothers, present motherhood’: motherhood practices in camera-based one-dimensional home spaces in urban China - Yunhong, Lyu; Zainudin, Sharifah Sofiah Syed; Sim, Ng Boon (John Wiley and Sons, 2026)
This paper examines the impact of home cameras on the home space and the performance of mothering duties in urban China. Based on in-depth interviews with 17 participants in China (6 mothers and 11 children), the study finds that home cameras produce a one-dimensional home space, characterised by asymmetrical visibility between mothers and children, grounded in maternal authority. This asymmetrical visibility enables mothers to fulfil duties remotely, while simultaneously infringing upon children's privacy. Children may either comply with the mother's remote surveillance and behave well or resist this asymmetrical visibility. In some cases, children's resistance leads to negotiations between mothers and children over boundaries of visibility and spatial autonomy, introducing new conflicts and additional burdens on long-distance motherhood. Using home cameras as a case study, this study expands the understanding of mediated motherhood and children's geographies through the lens of spatial production and visibility.